FAKTOR-FAKTOR YANG MEMPENGARUHI PEMAHAMAN UMKM DALAM PENYAJIAN LAPORAN KEUANGAN BERDASARKAN SAK EMKM PADA UMKM DI KELURAHAN JAKASETIA - Delvin Kautsar; Dewi Rejeki (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2020)
To find out how much the influence of the giving information and socialization, educational background, level of education, size of enterprises and enterprises long on the understanding of MSMes in drawing up financial statements based on the SAK EMKM. This research was carried out on 75 SMES in Jakasetia Sub-district using the questionnaire as a data retrieval method. Data was analyzed using multiple regression analysis that processed it through SPSS 25.0 application software The result of the t-test showed that the giving information and socialization, educational background, level of education, size of enterprises and enterprises long variables had a significant effect on the understanding of MSMes in drawing up financial statements based on the SAK EMKM. The conclusion of this study shows that the variable the giving information and socialization, educational background, level of education, size of enterprises and enterprises long has a significant effect on the understanding of MSMes in drawing up financial statements based on the SAK EMKM.